Cloning and expression analysis of manganese peroxidase and laccase transcripts from Ganoderma boninense PER71 in response to different nitrogen sources, phytohormones and hydrogen peroxide - Ho, Pei Yin (2019)
Basal Stem Rot (BSR) is a serious disease caused by Ganoderma species. Ganoderma boninense produces lignin degrading enzymes (LDEs) that are able to degrade the lignin component of plant cell wall causing oil palms to rot and eventually collapse. The transcripts and expressions of LDEs including manganese peroxidase (MnP) and laccase (Lac) in G. boninense PER71 during oil palm-Ganoderma interaction have not been reported. Likewise, the effect of nitrogen sources in fertilizers, phytohormones and hydrogen peroxide on the growth and gene expression of G. boninense are unknown. Therefore, the objectives of this study were to clone the transcripts encoding these LDEs; to measure their gene expression in G. boninense PER71 treated with different nitrogen sources (ammonium sulphate, ammonium nitrate, sodium nitrate and potassium nitrate), phytohormones (jasmonic acid, JA and salicylic scid, SA) and hydrogen peroxide; and to evaluate the effect of different nitrogen sources on the in vitro growth of G. boninense and oil palm seedlings inoculated with G. boninense. The full-length cDNA of four MnPs and three Lacs were cloned from G. boninense by Rapid Amplification of cDNA Ends (RACE)-PCR and confirmed by sequence analysis. Real-time reverse transcription-PCR (qRT-PCR) analysis showed that only Unigene 6011 (MnP) from G. boninense was upregulated by all nitrogen sources and hydrogen peroxide but down-regulated in JA treatment. Unigene 87 (MnP) showed up-regulation in G. boninense treated with JA. Unigene 35959 (MnP) of G. boninense was up-regulated by ammonium sulphate treatment, down-regulated by hydrogen peroxide and suppressed by sodium nitrate and SA. Meanwhile, Unigene 30636 (Lac) was up-regulated by SA; down-regulated by hydrogen peroxide and suppressed by ammonium sulphate, potassium nitrate and JA. Unigene 36023 (Lac) was up-regulated by JA and hydrogen peroxide while Unigene 90667 (Lac) was up-regulated by ammonium nitrate, JA, SA and hydrogen peroxide. The growth of G. boninense cultured on ammonium nitrate-containing Czapek-Dox agar was the fastest while the growth on sodium nitrate was the slowest based on the measurement of radial mycelial diameter. The optical mycelial density of G. boninense cultured on ammonium nitrate was also denser than that of G. boninense cultured on sodium nitrate. However, the highest optical mycelial density was observed for G. boninense cultured on ammonium sulphate. On the other hand, G. boninense-infected oil palm seedlings treated with ammonium nitrate were the least infected; white mycelia were not observed at the basal region and root surface as compared to oil palm seedlings in other nitrogen treatments. Inoculated oil palm seedlings without additional nitrogen; treated with ammonium sulphate, sodium nitrate and potassium nitrate showed increased disease symptoms. The most serious disease symptoms were observed in oil palm seedlings without nitrogen supplement, followed by sodium nitrate and potassium nitrate, ammonium sulphate then ammonium nitrate. The results showed that ammonium nitrate is a preferable source of nitrogen for growth of G. boninense and could slow down BSR development. In conclusion, the study contributes to the basic understanding of the effects of different nitrogen sources, phytohormones and hydrogen peroxide on G. boninense and the expression of MnP and Lac, as well as the disease development of BSR in oil palm seedlings.